THE EFFECTIVENESS OF GAME-BASED COLLABORATIVE LEARNING ON JUNIOR HIGH SCHOOL STUDENTS’ NARRATIVE READING COMPREHENSION - Sharla Febriana Mutia Yahya; Anik Nunuk Wulyani; Hasti Rahmaningtyas (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
Game-Based Collaborative Learning incorporates peer interaction with motivational game elements to support students’ engagement and reading development, grounded in social constructivist theory, collaborative learning, and game-based learning principles. Previous research has widely examined game-based learning and collaborative learning independently, while studies integrating both approaches for narrative reading comprehension at the junior high school level remain limited, particularly in Indonesia. This study explores the effectiveness of game-based collaborative learning in improving eighth-grade students’ reading comprehension of narrative texts. A quasi-experimental design was employed involving two classes. The experimental group engaged in game-based collaborative learning activities, including Narrative Puzzle, Kahoot!, and Narrative Video Detective, whereas the control group received the conventional method. Data were collected using pre-tests and post-tests and analyzed with IBM SPSS 23. The findings indicate that this method improves reading comprehension, engagement, motivation, and collaboration. Pedagogically, incorporating structured game-based collaborative activities into reading lessons can effectively enhance learning and classroom engagement, making game-based collaborative learning a practical instructional strategy for secondary education.